An industrial quality control study on PSP Manufacturing Company Inc. - Baterina, Eunessa; Cortez, Kahna Lynelle G.; Dolor, Katherine Z. (Diliman, Quezon City College of Engineering, 2002)
PSP Manufacturing Inc., is a major producer of Polypropylene, Polyethylene and Nylon ropes, twines and nets in the country. The company manufactures these products by order from various fields of the industry such as agriculture - farming, fishing, shipping and even in households and handicrafts. Being one of the competitive manufacturing companies of these products in the country, PSP aims to continually improve its performance to maintain and increase its market share, especially now that they are entering the global market. One important factor is to improve its manufacturing processes, particularly their most demanded product line-Polypropylene products, whose customers are very particular in the strength of these products. Critical steps for improving the quality of the products are analysis of the production processes, identification of possible sources of defects and nonconformities, and statistical control of these quality points. Problem Identification Tools such as Failure Mode Effects and Criticality Analysis and Statistical Process Control tools were used to determine the major causes of defects or nonconformities. From these tools, the twisting process was discerned to be the major cause of most of the defects (unbalanced twist and joined strands) of the products. From the Problem Analysis, it was identified that the three major problems of the company were Ropes with Unbalanced Twist, Unbalanced Twist with Jointed and Unbalanced Twist with Kinky Strands. It was also identified that the root causes of these problems are the poor condition of the machines due to age, the orientation of the strand bobbins on the laying machine and the varying sizes of the filaments caused at the extrusion process. The Statistical Process Control used was the control charts for variables and attributes, specifically the pChart and the Xbar and R Chart. The last 2 charts plotted by the group shows that the company's process is out of control. However, it has the potential of being capable so that improvements in the process as well as closer monitoring may lead to a more efficient process. The group recommends the company to install tension controllers on their laying machines and replace the filters in their extruders twice a week to improve their process. In addition to this, the group also recommends the company to use Statistical Quality Control in the way they monitor their process.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: PSP Manufacturing Incorporated; Rope trade; Quality control